Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content: 1. The role of faculty members in promoting the culture of dialogue in the university environment from the point of view of students at the University of Hafr Al-Batin Mrs. Budur Gasem Alshuraya 2. The practice of primary school mathematics teachers of blended learning in the educational process in Dawadmi Governorate Mr. Saad Farhan Mohammed Al-Otaibi 3. Teacher Professional Development in Light of the Saudi Vision 2030 and International Experiences Mrs. Afnan Fayiz Awad Altalhy , Mrs. Afnan Omar Masoud , Mrs. Taghreed Abdu Homdi , Mrs. Faridah Rashid Alqithami , Mrs. Nora Abdulaziz Alharbi , Mrs. Dalal Mutlaq Alamrani , Mrs. Reem Khudher Alsaadi, Mrs. Maraam Misri Alutaybi 4. Perceptions of social studies teachers about the role of strategic intelligence in supporting decision-making in pre-university education institutions and its impact on sustainable competitiveness Mrs. Muna Rashid Al-Na’aimi 5. The level of first year secondary students in the Kingdom of Saudi Arabia in critical speaking skills Prof. Mahmoud Helal Abdelkader 6. Social support and its relationship to psychological well-being among tenth grade students in the governorates of Gaza Dr. Doaa Salim Ali Al-Kayal 7. The level of Critical thinking of Mathematical students in Faculty of Education- Sana’a University Mrs. Bushra Abdalaleem Al-Usofi, Co-Prof. Dhekra Mohammed Al-baqeri 8. The degree of Availability of the Global mathematics standards in the Geometry axis in the mathematics books of (1 st - 4th) grades, from the point of view of female teachers in the Sultanate of Oman Dr. Mohammed Nassir Saif Alriyami